Can Social Safety Net (SSN) Tackle Poverty During Covid-19 Pandemic in Tabalong Regency? - Sari Ayutyas; Iqbal Miftakhul Mujtahid; Mani Festati Broto (Budapest International Research and Critics University, 2022)
The recent enhancement in poverty has occurred because of the COVID-19 pandemic. The government designed several policies to protect vulnerable populations and reduce poverty. One policy was the social safety net program (SSN). The effectiveness of the SSN program in reducing poverty contains academic debates. On the one hand, the research results showed no influence of the SSN on poverty reduction. So this study aims to analyze poverty in the Tabalong Regency. This research used primary data. Binomial Logistics Regression was employed in the analysis. Model testing included control variables represented by the number of household members, age, gender, education, and occupation of the primary household member. Simultaneous model testing results showed that the SSN program affected poverty in Tabalong Regency. Partially model testing results showed that not all SSN programs affect poverty in Tabalong Regency. Only the SSN program of Village Fund Direct Cash Assistance and Regional Government Routine Social Assistance involved poverty. In addition, the control variables also affected the chances of a household being poor or not poor, except for the age variable. The odds ratio value meant that households receiving these two programs had 0.283 and 0.370 times the probability of being not poor.